Health Communication in Patient Handling at The Emergency Department of The General Hospital Dr. H. Yulidin Away South Aceh District - Anis Seroja; Rani; Azman (Winaya Inspirasi Nusantara Foundation, 2019)
This study was conducted to look at health communication in patient management in the emergency department, where health communication is very important in providing action to emergency patients. Because if there is an error in communication, it will cause fatal to the patient. This research was conducted at the Emergency Department of Dr. H. Yulidin Away General Hospital. The method in this study uses qualitative methods with data collection techniques through observation, interviews, and observation. The subjects of this study were 18 people, of which 3 doctors, 5 nurses, 4 patients and 6 patients' families. The results of this study indicate that communication in patient management between medical personnel with patients and patients' families is effective in providing information. There are two types of communication used, namely verbal communication used such as oral communication that is easily understood by patients and families of patients, while nonverbal communication such as smiles, using soft voice intonations, and happy facial expressions when visiting patients so as to make patients feel comfortable with the services provided by medical personnel. In addition, in the Emergency Department, communication used to patients and families of patients can reduce and even eliminate the panic of patients who enter the emergency room in a critical and panic state, medical personnel tend to communicate so that patients and families of patients are calmer.